2021
DOI: 10.1111/ner.13324
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of a Novel Spinal Cord Stimulation Clinical Workflow Using Kilohertz Stimulation: Twelve-Month Results From the Vectors Study

Abstract: Background and Objectives: Multiple variables play a role in spinal cord stimulation (SCS) treatment outcomes, including patient anatomy, pain pattern, lead location, stimulation parameters, and so on. A wide range of stimulation parameters are considered safe and on-label, and as a result a growing number of new frequencies and frequency-combinations are being incorporated into standard practice. A standardized approach to therapy delivery may provide more consistent outcomes for more patients. The Vectors st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The efficacy of using the Evolve workflow involving stimulating at 1 kHz with a pulse width from 90–220 µs was demonstrated in the Vectors study. 60 Differential Target Multiplexed (DTM) SCS uses electrical signals and multiple anatomical targets to target neurons and glial cells differently to balance neuro-glial interaction and optimize neuromodulation outcomes. The DTM RCT 61 showed a superior effect on back pain and leg pain treatment using DTM SCS versus tonic stimulation.…”
Section: Results: Consensus Statements and Evidencementioning
confidence: 99%
“…The efficacy of using the Evolve workflow involving stimulating at 1 kHz with a pulse width from 90–220 µs was demonstrated in the Vectors study. 60 Differential Target Multiplexed (DTM) SCS uses electrical signals and multiple anatomical targets to target neurons and glial cells differently to balance neuro-glial interaction and optimize neuromodulation outcomes. The DTM RCT 61 showed a superior effect on back pain and leg pain treatment using DTM SCS versus tonic stimulation.…”
Section: Results: Consensus Statements and Evidencementioning
confidence: 99%
“…SCS is widely used for treating chronic intractable pain [ 7 ], and randomized controlled trials (RCTs) comparing SCS with conservative treatment and repeated surgery for low back pain and leg pain due to FBSS have shown the advantage of SCS [ 8 10 ]. While conventional paresthesia-based SCS with low-frequency stimulation is still commonly used, recently introduced stimulation methods, such as burst SCS [ 11 , 12 ], 10 kHz high-frequency therapy [ 13 , 14 ], high-dose SCS [ 15 , 16 ], high-density SCS [ 17 , 18 ], closed-loop SCS [ 19 , 20 ], and differential target multiplexed programming [ 21 , 22 ], have been reported to be equally or more effective than paresthesia-based SCS. Also, spinal cord stimulator implantation using anatomical placement in which electrodes are placed mainly in the T9/10 intervertebral space has comparable therapeutic efficacy with paresthesia-based SCS but shorter operative time [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 Besides Con-SCS, new SCS paradigms like High-Frequency (HF) and Differential Target Multiplexed (DTM)-SCS have recently emereged. 12 , 13 A clinical study has been performed using HF SCS in PDPN patients which showed promising result. 14 DTM-SCS could potentially further improve pain reduction and responder rates.…”
Section: Introductionmentioning
confidence: 99%